IMPROVING THE ACCOUNTING OF FUNDS OF THE DIRECTOR'S FUND IN PUBLIC EDUCATIONAL INSTITUTIONS (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, the need and importance of the formation of funds of the director's fund in the effective implementation of the activities of public educational institutions is theoretically based. The basics of accounting and control of funds of the director's fund in public educational institutions are outlined. Practical aspects of organizing and maintaining the accounting of funds of the director's fund of public educational institutions are investigated. The state of implementation of control measures to ensure the reliability of information on the use of director's fund funds in public educational institutions is analyzed. The author's suggestions on improving the accounting of funds of the director's fund in public educational institutions were formed.